Nutrition, oxidative stress and intestinal dysbiosis: Influence of diet on gut microbiota in inflammatory bowel diseases - Tomasello, Giovanni; Mazzola, Margherita; Leone, Angelo; Sinagra, Emanuele; Zummo, Giovanni; Farina, Felicia; Damiani, Provvidenza; Cappello, Francesco; Gerges Geagea, Alice; Jurjus, Abdo; Bou Assi, Tarek; Messina, Massimiliano; et al. (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2016)
BACKGROUND: Microbiota refers to the population of microorganisms (bacteria, viruses and fungi) that inhabit the entire gastrointestinal tract, more particularly the colon whose role is to maintain the integrity of the intestinal mucosa and control the proliferation of pathogenic bacteria. Alteration in the composition of the gut microbiota is called dysbiosis. Dysbiosis redisposes to inflammatory bowel diseases such as ulcerative colitis, Crohn disease and indeterminate colitis. METHODS: The purpose of this literature review is to elucidate the influence of diet on the composition of the gastrointestinal microbiota in the healthy gut and the role of diet in the development of dysbiosis. CONCLUSION: The "Western diet", in particular a low - fiber high fat/high carbohydrate diet is one factor that can lead to severe dysbiosis. In contrast, "mediterranean" and vegetarian diets that includes abundant fruits, vegetables, olive oil and oily fish are known for their anti-inflammatory effects and could prevent dysbiosis and subsequent inflammatory bowel disease.
Keywords: Oxidative Stress; idiopatické střevní záněty; dieta; nutriční stav; Inflammatory Bowel Diseases; Nutritional Status; lidé; Dysbiosis; Diet; oxidační stres; střevní mikroflóra; dysbióza; Gastrointestinal Microbiome; Humans